Weather related risks in Belgian arable agriculture. (January 2018) - Gobin, A.
Abstract: Agricultural production risk is to a great extent determined by weather conditions. The research hypothesis was that adverse weather conditions during sensitive crop stages do not entirely explain low arable yields. The temporal overlap between weather conditions and crop stages in the arable cropping system was determined using a modelling framework that couples phenology to the soil water balance and crop growth. While climatic constraints have changed on average over time, block maxima of indicators during crop growth stages showed no trends, except for minimum temperature related indicators, owing to a dual shift in both phenology and weather conditions. Return periods were derived for adverse weather conditions such as frost, drought, heat and waterlogging, and for general weather conditions such as radiation, temperature, precipitation and the water balance using fitted statistical distributions for the period 1947–2012. Distributions fitted to detrended yields allowed relating weather conditions during the growing season to the lower and upper quintiles of the yield distributions. Weather conditions varied significantly between years, crops and growth stages. Results for winter wheat, winter barley, winter oilseed rape, grain maize, potato and sugar beet in Belgium demonstrated that the impact of single events on crop yields was difficult to capture, as yields integrated weather variability during the growing season and crops recovered from adverse weather conditions. The approach of combining physically based crop modelling with statistical distribution fitting to characterise the tail ends within the range of observations of both crop yields and weather conditions showed that water (drought and waterlogging) and temperature (frost and heat) stress resulted in low arable yields when they occurred either in concatenation or in combination with adverse weather conditions such as low radiation during the growing season. The method helped quantify agricultural production risks and rate both weather and crop-based agricultural insurance. Highlights: Crop-weather interactions were captured using a physically based crop modelling approach. 20-year return values were established for weather events occurring during different stages of the growing season. Weather related stress varied significantly between years, crops and growth stages. Multiple adverse weather conditions explained low (high) yields, defined as the 20% lower (upper) tail of the yield distribution.